PENERAPAN AKUNTANSI PPh PASAL 23 ATAS JASA AGEN PADA PT. AJB BUMIPUTERA 1912 CABANG MANADO - Luas, Cicilia; Runtu, Treesje; Tirayoh, Victorina Z. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
In the state budget of revenues and expenditures (APBN), it can be seen that the target of state revenue from the tax sector has increased from year to year. APBN 2016 shows tax revenue accounted for about 84% of total state revenues as a whole. Therefore, Canit is said that taxes play a vital role in the financing of national development. Object in this research is PT. AJB BUMIPUTERA 1912 which is engaged in life insurance. The purpose of this study is to find out how the application of accounting PPh article 23 for servicesagent at PT. AJB BUMIPUTERA 1912 Manado branch. Method of data analysis used in this research is discussing problem by colleting, elaborating, counting, and comparing a situation and explaining a situation so that can be drawn conclusion.Keywords: accounting, income tax article 23